Brahmatatvaprakāśikā nāma Brahmasūtravṛttiḥ - Sadāśivendra Sarasvatī ca. 18. Jh. (Sanskrit Academy series, 2012)
Classical commentary, with supercommentary, on Brahmasūtra, basic work of the Vedanta school in Indic philosophy by Bādarāyaṇa